Manufacturable insight into modelling and design considerations in fibre-steered composite laminates: state of the art and perspective - Aragh, B. Sobhani; Farahani, E. Borzabadi; Xu, B. X.; Ghasemnejad, Hessam; Mansur, W. J. (Elsevier, 2021)
The advent of novel robot-assisted composite manufacturing techniques has enabled steering of fibre paths in the plane of the lamina, leading to the emergence of the socalled variable angle tow (VAT) composite laminates. These laminates, with spatially varying fiber angle orientations, provide the designer with the ability to tailor the pointwise stiffness properties of VAT composites with substantially more efficient structural performance over conventional straight fibre laminates. As the application of fibresteered composite laminates has reached an unprecedented scale in both academia and industry in recent years, a reflection upon the state-of-the-art advancements in the modelling, design, and analysis of these advanced structures becomes vital for successfully shaping the future landscape. Motivated by the gap and shortcomings in the available review works, in the present paper, firstly underlying fibre placement technologies including tailored fiber placement (TFP), continuous tow shearing (CTS), and automated fibre placement (AFP) are presented and discussed in detail. Afterwards, mathematical models of reference fibre path in fibre--steering technology will be reviewed, followed by providing a discussion on the manufacturing limitations and constraints of the AFP process. Then, design considerations in constructing a ply with multiple courses are elaborated and key techniques to fill the entire layer with several courses are reviewed. This review is then followed by an introduction to the continuity and smoothness of fiber paths. Furthermore, a description on the material and geometric uncertainties is elaborated. Last but not least, the plate and shell laminate theories, which establish the fundamental core of the modelling and design of VAT composite structures, will be discussed.
Keywords: Variable stiffness; Manufacturing constraints; Modelling and design; Fibre placement technologies; Lightweight composite structures; Variable angle tow